Fabrication of phytic acid sensor based on mixed phytase-lipid Langmuir-Blodgett films - Caseli, Luciano; Moraes, Marli L.; Zucolotto, Valtencir; Ferreira, Marystela; Nobre, Thatyane M.; Zaniquelli, Maria Elisabete D.; Rodrigues Filho, Ubirajara P.; Oliveira, Osvaldo N. (Amer Chemical Soc, 2006)
This paper reports the surface activity of phytase at the air-water interface, its interaction with lipid monolayers, and the construction of a new phytic acid biosensor on the basis of the Langmuir-Blodgett (LB) technique. Phytase was inserted in the subphase solution of dipalmitoylphosphatidylglycerol (DPPG) Langmuir monolayers, and its incorporation to the air-water interface was monitored with surface pressure measurements. Phytase was able to incorporate into DPPG monolayers even at high surface pressures, ca. 30 mN/m, under controlled ionic strength, pH, and temperature. Mixed Langmuir monolayers of phytase and DPPG were characterized by surface pressure-area and surface potential-area isotherms, and the presence of the enzyme provided an expansion in the monolayers ( when compared to the pure lipid at the interface). The enzyme incorporation also led to significant changes in the equilibrium surface compressibility (in-plane elasticity), especially in liquid-expanded and liquid-condensed regions. The dynamic surface elasticity for phytase-containing interfaces was investigated using harmonic oscillation and axisymmetric drop shape analysis. The insertion of the enzyme at DPPG monolayers caused an increase in the dynamic surface elasticity at 30 mN m(-1), indicating a strong interaction between the enzyme and lipid molecules at a high-surface packing. Langmuir-Blodgett (LB) films containing 35 layers of mixed phytase-DPPG were characterized by ultraviolet-visible and fluorescence spectroscopy and crystal quartz microbalance nanogravimetry. The ability in detecting phytic acid was studied with voltammetric measurements.